Transformation, Morphology, and Dissolution of Silicon and Carbon in Rice Straw-Derived Biochars under Different Pyrolytic Temperatures - Xiao, Xin; Chen, Baoliang; Zhu, Lizhong (Environmental science & technology, 2014)
Biochars are increasingly recognized as environmentally friendly and cheap remediation agents for soil pollution. The roles of silicon in biochars and interactions between silicon and carbon have been neglected in the literature to date, while the transformation, morphology, and dissolution of silicon in Si-rich biochars remain largely unaddressed. In this study, Si-rich biochars derived from rice straw were prepared under 150–700 °C (named RS150-RS700). The transformation and morphology of carbon and silicon in biochar particles were monitored by FTIR, XRD, and SEM-EDX. With increasing pyrolytic temperature, silicon accumulated, and its speciation changed from amorphous to crystalline matter, while the organic matter evolved from aliphatic to aromatic. For rice straw biomass containing amorphous carbon and amorphous silicon, dehydration (<250 °C) made silicic acid polymerize, resulting in a closer integration of carbon and silicon. At medium pyrolysis temperatures (250–350 °C), an intense cracking of carbon components occurred, and, thus, the silicon located in the inside tissue was exposed. At high pyrolysis temperatures (500–700 °C), the biochar became condensed due to the aromatization of carbon and crystallization of silicon. Correspondingly, the carbon release in water significantly decreased, while the silicon release somewhat decreased and then sharply increased with pyrolytic temperature. Along with SEM-EDX images of biochars before and after water washing, we proposed a structural relationship between carbon and silicon in biochars to explain the mutual protection between carbon and silicon under different pyrolysis temperatures, which contribute to the broader understanding of biochar chemistry and structure. The silicon dissolution kinetics suggests that high Si biochars could serve as a novel slow release source of biologically available Si in low Si agricultural soils.